Penerapan Model Pembelajaran Project-Based Learning pada Pengajaran Listening - Yulia Nur Ekawati; Noeris Meiristiani; Anin Eka Sulistyawati (Cakrawala: Jurnal Pendidikan, 2018)
Learning (PBL) model in teaching Listening. Sample was fourth semester students of Universitas Pancasakti Tegal. The research instruments were documentation (recording) and questionnaire. Recording was used to explain the implementation of PBL model in teaching Listening. While questionnaire was used to find out students’ respond. Researchers analysed the result of recording based on the steps of implementing PBL model. Moreover, to analyse the questionnaire data, researchers used table and percentage of students’ responds of agreement level toward the implementation of PBL model in Listening class. The result of recording explored steps of implementing PBL model i.e.: (1) deciding a topic of lesson, (2) making group, (3) doing tasks, (4) planning a presentation, (5) performing a presentation, and (6) evaluation. The result of questionnaire showed the positive respond of implementing PBL model in Listening class with the students’ respond level was 90,5%. According to data, it could be concluded that PBL model could be applied in Listening class.